Vera. Set 9 [videorecording (DVD)] - Blethyn, Brenda, 1946-; Doughty, Kenny, 1975-; Morrison, Jon (BBC, 2019)
The central character is Detective Chief Inspector Vera Stanhope. Who is obsessive about her work and driven by her own demons. If she's lonely she doesn't show it and faces the world with caustic wit, guile, and courage. Her trusted an dlong suffering colleague is Sergeant Joe Ashworth. Together they approach every new case with unparalleled gusto and professionalism.